Correlation between Early Postoperative Urine Output and One-Year Graft Function after Living Donor Kidney Transplantation: A Prospective Observational Study - Luitel, Bhojraj; Tamang, Rabindra; Chalise, Pawan Raj; Chapagain, Suman; Poudyal, Sujeet; Pradhan, Manish Man (Journal of Institute of Medicine Nepal, 2025)
Introduction The prognostic value of early postoperative urine output after kidney transplantation remains uncertain. This study evaluates its association with one-year graft function and examines additional clinical predictors. Methods A prospective observational study was conducted at a tertiary transplant center in 90 renal transplant recipients; 82 completed one-year follow-up. Primary outcome was one year estimated glomerular filtration rate (eGFR) by Chronic Kidney Disease Epidemiology Collaboration 2021. Exposures included urine output on postoperative days 1 to 3, donor age, warm and cold ischemia times, discharge creatinine, dialysis duration, human leukocyte antigen mismatch, and early surgical complications within 30 days. Primary analysis used linear regression with prespecified covariates. Secondary analysis used logistic regression for eGFR less than 60 mL per minute per 1.73 m2. Results Urine output on postoperative days 1, 2 and 3 did not correlate with one year estimated glomerular filtration rate. Complications occurred in 8.5 % (7/82). Body mass index showed no association with one year estimated glomerular filtration rate. In the multivariable model, older donor age and higher discharge creatinine independently associated with lower one year estimated glomerular filtration rate (donor age B = -0.595, p = 0.02; discharge creatinine B = -0.219, p = 0.03). Single-marker receiver operating characteristic analysis showed poor discrimination. Conclusion Early post-operative urine output did not correlate with one-year graft function. Future research should focus on additional markers and strategies to improve graft function prediction.